Sequential generation of linear cluster states from a single photon emitter - Istrati, D.; Pilnyak, Y.; Loredo, J. C.; Antón, C.; Somaschi, N.; Hilaire, P.; Ollivier, H.; Esmann, M.; Cohen, L.; Vidro, L.; Millet, C.; Lemaître, A.; et al. (Nat Commun, 2020)
Light states composed of multiple entangled photons—such as cluster states—are essential for developing and scaling-up quantum computing networks. Photonic cluster states can be obtained from single-photon sources and entangling gates, but so far this has only been done with probabilistic sources constrained to intrinsically low efficiencies, and an increasing hardware overhead. Here, we report the resource-efficient generation of polarization-encoded, individually-addressable photons in linear cluster states occupying a single spatial mode. We employ a single entangling-gate in a fiber loop configuration to sequentially entangle an ever-growing stream of photons originating from the currently most efficient single-photon source technology—a semiconductor quantum dot. With this apparatus, we demonstrate the generation of linear cluster states up to four photons in a single-mode fiber. The reported architecture can be programmed for linear-cluster states of any number of photons, that are required for photonic one-way quantum computing schemes.
Publisher: Nature Publishing Group
Keywords: quantum information; Quantum optics; Single photons and quantum effects